Ultrastructure, development, and homology of insect embryonic cuticles - Konopová, Barbora; Zrzavý, Jan (Journal of morphology, 2005)
Ultrastructure and deposition of the cuticles secreted by embryos representing eight insect orders were examined by transmission and scanning electron microscopy. Embryos of the apterygote silverfish Thermobia domestica deposit two embryonic cuticles. Deposition of the first (EC1) is initiated at the beginning of appendage development when the intercalary segment and the neural groove are clearly visible. This cuticle lacks surface microsculpture and consists of an outer epicuticle and an underlying fibrous layer, thought to represent procuticle. At the time of dorsal closure, deposition of a second embryonic cuticle (EC2) begins; this bears sensilla and functions in the first instar larva. In representative embryos of seven pterygote orders (Ephemeroptera, Odonata, Plecoptera, Neuroptera, Coleoptera, Lepidoptera, and Mecoptera), three cuticles were found to be secreted. The first cuticle in pterygotes is homologous to EC1 of T. domestica, but consists solely of outer epicuticle. EC2, the "prolarval cuticle," bears a characteristic surface microsculpture in embryos of some species and egg-teeth and other hatching devices, and consists of outer and inner epicuticles and a more or less reduced procuticle. EC2 is reduced in the embryos of derived endopterygotes, where a procuticle is lacking and the inner epicuticle is reduced. After hatching, when EC2 is shed, the first instar larva is covered by a third embryonic cuticle (EC3), whose deposition was initiated while the insect was still within the egg. Presence of only two embryonic cuticles in cyclorrhaphous flies is due to the total loss of prolarval cuticle. Investigated exopterygote and endopterygote insects excluding flies thus deposit three embryonic cuticles, and their juveniles (exopterygote "nymphs"; endopterygote "larvae") seem to hatch at equivalent stages of development. Differences between the modes of cuticulogenesis in silverfish and pterygote embryos suggest that the apterygote first larval instar was embryonized and became a fully embryonic prolarva in pterygotes.
Keywords: Insecta; embryo nesavčí; Biological Evolution; Animals; Microscopy, Electron, Scanning; hmyz; Embryo, Nonmammalian; Metamorphosis, Biological; Phylogeny; biologická proměna; zvířata; fylogeneze; biologická evoluce; mikroskopie elektronová rastrovací